2019
DOI: 10.3390/agronomy9070383
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Drying Methods on Water-Soluble Carbohydrates and Crude Protein Concentrations and Their Ratio in Two Perennial Ryegrass Cultivars

Abstract: The objective of this study was to assess the joint effect of perennial ryegrass cultivars and drying methods on concentrations of water-soluble carbohydrates (WSC) and crude protein (CP) and WSC/CP ratio. AberMagic AR1 and Expo AR1 forage were collected in December 2016, March, June, September and November 2017 and either oven-dried at 60 °C for 48 h (OD_60), at 80 °C for 16 h (OD_80), frozen at −80 °C for 48 h then freeze-dried (−80_FD), or flash-frozen with liquid N then freeze-dried (LN_FD). Data were anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 53 publications
(67 reference statements)
1
1
1
Order By: Relevance
“…From previous literature, AberMagic has shown a greater WSC and CP concentration in the fresh forage when compared with other ryegrass cultivars (Chen et al, 2016;Moscoso et al, 2019;Wang et al, 2020). In the present experiment, the WSC concentration of the standing forage before being cut for silage was numerically higher for RG-WC and MRG compared to PP (Supplementary Table S3).…”
Section: Discussionsupporting
confidence: 59%
“…From previous literature, AberMagic has shown a greater WSC and CP concentration in the fresh forage when compared with other ryegrass cultivars (Chen et al, 2016;Moscoso et al, 2019;Wang et al, 2020). In the present experiment, the WSC concentration of the standing forage before being cut for silage was numerically higher for RG-WC and MRG compared to PP (Supplementary Table S3).…”
Section: Discussionsupporting
confidence: 59%
“…A study performed in Chile evaluating HSG and standard PRG cultivars submitted to contrasting agronomic management systems (applying the same N fertilisation rates and defoliation frequencies as the present study) reported no consistent expression of the "high-sugar" trait [10]. Another study carried out in similar climate conditions as the current work did not show an expression of the high-sugar trait in diploid PRG cultivars selected for high WSC content defoliated at the stage of three leaves per tiller [27].…”
Section: Nutritional Composition Of Foragecontrasting
confidence: 45%
“…However, it must be noted that the current LS treatment was not ‘low sugar’ and, in comparison with other studies investigating high sugar grasses, was higher than most high sugar treatments [ 42 ]. The fact that, after harvesting, the samples were immediately frozen in the field and further freeze-dried could have reduced WSC losses due to respiration [ 43 , 44 ]. In the case of the LS cultivar (Extreme), the high WSC in spring may be due to its phenological stage, as it begins flowering earlier than the HS cultivar (Expo), and therefore increases its WSC [ 14 ].…”
Section: Discussionmentioning
confidence: 99%